Os direitos sociais no debate sobre a natureza econômica dos governos Lula e Dilma - Santos, Julio Cesar Silva (2015)
His research deals with the concepts of neoliberalism, details the stages of the neoliberal model, makes considerations about the economic nature of Brazil, specifies neoliberal policies during the FHC administration and describes the transition of developmentalism to what we call "neo-developmentism" ideological trend it claims exist in the Lula and Dilma governments, a post-neoliberal front , which did not break with the capitalist model, but developed the popular layers beneficial policies. The fruit of this work, research if governments called neodesenvolvimentistas, performed the more focused liberalism to social or not, and to identify the impacts of public policies on social and economic area.